SIFAT PENGERINGAN ALAMI DAN DEHUMIDIFIKASI BEBERAPA JENIS KAYU INDONESIA - Syarif Hidayat; Suparman Karnasudirdja (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
This paper presents results of laboratory study on the rate of moisture content decrease of 19 timber species. The test specimen from each species were subjected to air drying under sheltered condition (under roof) and drying in a dehumidifying chamber. At the end of each test. the defect of each specimen was recorded, and the most appropriate form of relation between duration of drying and moisture content decrease was sought.From data analysis it was shown that a power form of relationship (Y = aXb) was reasonable, with coefficient of correlation values varying between 0.80-0.90.The result also shows that the longest air drying time (from 60% to 20% moisture content) was recorded by kayu besi (53 days) and the shortest by dama-dama and palapi (18 days).As has been anticipated, drying in the dehumidifier has reduced considerably the time required for drying from 60% to 20% moisture content. For example for the three species mentioned above the figures were 20 days for kayu besi and 5 days for dama-dama and palapi.The result shows further that severe defect was observed in kolaka, bugis, suling and belu itam. The remaining species have either moderate or slight defect.